Outcome of kidney transplantation from very senior donors in Switzerland – a national cohort study. (5th March 2021) - Kuhn, Christian; Lang, Brian M.; Lörcher, Sylvia; Karolin, Andrea; Binet, Isabelle; Beldi, Guido; Golshayan, Délaviz; Hadaya, Karine; Mueller, Thomas F.; Schaub, Stefan; Immer, Franz; Stampf, Susanne; et al.
Summary: Kidney transplantation from older and marginal donors is effective to confront organ shortage. However, limitations after transplantation of kidneys from very marginal kidney donors remain unclear. We compared patient and graft outcome, achieved allograft function and quality of life of renal transplantations from Very Senior Donors (VSD, defined as donors aged 70 years and older) with Senior Donors (SD, aged 60–70 years) and Regular Donors (RD, aged younger than 60 years) in Switzerland. We evaluated the outcome of 1554 adult recipients of deceased donor kidney transplantations from 05/2008 to 12/2019; median follow‐up was 4.7 years. Failure‐free survival (freedom from graft loss or death), glomerular filtration rate (eGFR), and quality of life at 12 months were analyzed for RD (reference group, n = 940), SD ( n = 404), and VSD ( n = 210). Failure‐free survival decreased with increasing donor age, mainly attributable to premature graft loss. Still, overall 5‐year failure‐free survival reached 83.1%, 81.0%, and 64.0% in the RD, SD, and VSD subgroups, respectively. eGFR 12 months post‐transplantation was significantly higher in RD compared with SD and VSD. The acceptance rate of donor candidates for kidney TPL was 78% for the entire cohort (87% for RD, 79% for SD, and 56% for VSD). Deceased donor kidney transplantation from donors aged 70 years or older is associated with an inferior, yet acceptable failure‐free outcome, with sustained quality of life.